Application of Clean & Clear ® polymer film as a substrate for flexible and highly sensitive graphene–based strain sensor - Zulhelmi, Ismail (Elsevier B.V., 2020)
In the development of wearable electronics device, a low -cost substrate that is not only robust but also able to detect subtle human motion is widely sought after by many researchers. To achieve this objective, a commercial polypropylene film from Clean & Clear ® brand has been used as a substrate for the fabrication of sensitive strain sensor. The coating of graphene on the pre-treated PP film by layer-to-layer assembly impressively allows a detection of wrist pulse, finger bending and throat movement during pronunciation. The highly sensitivity of the reported strain sensor in this communication is reflected from the maximum computed gauge factor at ~1000.